A Real‐Time Prediction System of the Intensity of Solar Energetic Proton Events Based on a Solution of the Diffusion Equation - Y. Zhang; Y. Wang; X. Li; P. B. Zuo (Space Weather)
Abstract In this study, based on solar energetic particle (SEP) events classification and a solution of the diffusion equation, we present an efficient system, HITSEP, to predict the intensities in different energy channels (P4 15.0–44.0 MeV, P5 40.0–80.0 MeV, and P6 80.0–165.0 MeV) of energetic proton events observed by GOES spacecraft. The system can predict the rising phase (especially the peak time and peak intensity) of the energetic proton events using only a small amount of data at the beginning of the solar energetic proton events. Among the events that meet the conditions for the use of our prediction system from 2003 to 2017, for P4, P5, and P6 channels, the median Warning Times are 3.70, 2.52, and 1.69 hr; the median Error of the Intensity for events are 0.43, 0.23, 0.34 orders of magnitude; the median Error of the Peak Time for events are 2.53, 0.55, 0.43 hr, respectively. Our system is based on physical mechanisms and has a high accuracy in forecasting the peak intensity with a strict definition of the error. The HITSEP system has huge potential to apply in the space weather forecast. The application of the HITSEP system in space weather forecasting is very promising.